Small ruminant production in Ethiopia: Prospects for improving productivity - Tembely, S. (Ethiopian Society of Animal Production, 1998)
Sheep and goats are a major source of income (cash) and food protein for rural farmers in most part of the tropics. In spite of the numerical importance of small ruminants in Ethiopia, their productivity is still low due to poor management, diseases and indaequate nutrition. Direct and indirect losses occur through mortalities, reduced weight gain, poor reproductive performance and condemnation of diseased organs at the abattoir. This paper describes the main production systems (pastoral, mixed farming and smallholder farming systems) and the major constraints to small ruminant production in Ethiopia. It is suggested that effective control strategies of infectious diseases e.g. Peste des Petits Ruminants (PPR), Contagious Caprine Pleuro-Pneumonia (CCPP), Respiratory diseases and Parasitic diseases e.g. liver flukes and nematode infections, which are endemic and of paramount economic importance, could significantly contribute to the overall improvement of small ruminant productivity. An integrated approach towards sustainable disease control using a combination of chemotherapy, resistant indigenous breeds, improved nutrition, vaccination and environmental management based on the knowledge of the biology of the causative organisms and a sound understanding of the epidemiology of diseases in Ethiopia is discussed. Examples of such combination of the use of epidemiological information, pasture management and low cost supplements with medicated-molasse-urea blocks to control endoparasites in the highland sheep of Ethiopia are Reported.